(Nie)oczywiste potrzeby młodych Polek z endometriozą – egzemplifikacje i implikacje na podstawie badań własnych - Kwaśniewska, Anna; Kaźmierska, Marlena (Kultura-Społeczeństwo-Edukacja, 2024)
The aim of this article was to explore the experiences of women with endometriosis, identify their needs, and assess their perception of how these needs are being met, particularly in the context of institutional support. The study utilized a biographical method and a narrative-biographical technique, enabling an in-depth understanding of the participants’ individual experiences. The research sample consisted of 23 women aged 22 to 33 years, residing in both large cities and smaller localities, all diagnosed with endometriosis. The findings revealed that the most significant challenges faced by women with endometriosis include a prolonged diagnostic process, limited access to qualified specialists, and the lack of reimbursement for supportive therapies such as psychotherapy, physiotherapy, and diet therapy. Participants also expressed a need for greater emotional and social support to reduce feelings of isolation and stigmatization. Support groups and non-governmental organizations emerged as critical sources of assistance, bridging gaps in the public healthcare system. Recommendations derived from the study emphasize the need to develop the healthcare system by increasing the number of specialists, reducing waiting times for consultations, and introducing reimbursement for supportive therapies. Additionally, non-governmental organizations should intensify their educational and supportive activities, and social campaigns should focus on destigmatizing endometriosis.